Developing correlation map between learning styles, reading materials and creativity - Kassim, Hafizoah; Ali, Zuraina; Mohd Ali, Zarina; Mohd Radzuan, Noor Raha; Khamis, Nor Yazi (2008)
Many of the research in creativity were rooted in psychology and cognitive science; yet, of recent years, other disciplines of study such as business, management, education, and engineering began to put more weight on creativity. The value of creativity in engineering as in other disciplines is becoming essentially important, and most importantly, the synergy of these disciplines in spawning students as wellrounded multi-skilled creative individuals (Cropley, Priest & Cropley, 1997) is deemed crucial. Concepts such as creative thinking, creative behaviour, creative agent and sources of creativity have been the focal interests of research in understanding creativity, which have left researchers with more questions than answers. The researchers believe that reading materials also can be one of the sources that could enhance an individual's creativity. This study, therefore, attempts to investigate whether students' choice of reading materials as creative agent could enhance creativity. Since individuals are uniquely different in terms of personality, trait or characteristic, the researchers will also look at students' learning styles. Thus, by looking at the correlation between learning styles and choice of reading materials, how this relationship could enhance creativity can be discovered. This study was conducted in Universiti Malaysia Pahang (UMP) in which the respondents were UMP's engineering students randomly selected from all the five faculties. Torrence Test of Creative Thinking (TTCT) (Torrence, 1998), Learning Style Index (Felder & Silverman, 1988) and Researcher-Made Reading Materials Questionnaire were the instruments used. Hopefully, this can assist UMP students to be well-rounded multiskilled creative engineers, and help the university in materials development so that appropriate reading materials could be used to help students improve their creativity.